Screening selected actinobacteria for antifungal activity / Ezzatul Syahadah Zainordin - Ezzatul Syahadah, Zainordin (2011)
Actinobacteria are well known for their production of an extensive array of chemically diverse and medically important secondary metabolites. Fifty two strains of actinobacteria used in this study were divided into 20 colour groups based on their aerial and substrate mycelium colour as well as diffusible pigment production on Yeast Extract Malt Extract (ISP) medium. Antifungal activity was determined against Candida albicans, Candida parapsilosis, Fusarium oxysporum, Ganoderma boninense, Schizosaccharomyces pombe and Saccharomyces cerevisiae by the agar plug-diffusion method. Ten of the fifty two actinobacterial strains showed strong antifungal activity. Two strains (MA04119 and RHRS) were active against S. pombe, four strains (9, A21, OPSa and RC3) against S. cerevisiae, two strains (OPSa and A21) against C. albicans, one strain (MA04020) against C. parapsilosis, one strain (H23) against F. oxysporum and two strains (9 and PDA4) against G. boninense. The identification of actinobacterial strains were done by using molecular approaches including enterobacterial repetitive intergenic consensus (ERIC)-PCR and 16S rRNA gene sequencing. By using the (ERIC)-PCR fingerprinting technique, all the tested strains have been de-replicated into three groups. The ten actinobacterial strains which showed antifungal activity were also screened for the presence of polyene-specific CYP genes and only four of them (strains H23, RC3, MA04020, and RHRS) showed the presence of the expected 350bp DNA fragment of the polyene CYP internal region. This suggests that these four strains might produce the cryptic polyene biosynthetic compound. 16S rRNA gene sequence analysis showed that nine of the strains, (H23, RHRS, MA04119, MA04020, OPSa, RC3, PDA4, A12 and OPSa) belong to the genus Streptomyces, while strain 9 was identified to be a Brevibacterium sp.